2014
DOI: 10.4300/jgme-d-14-00161.1
|View full text |Cite
|
Sign up to set email alerts
|

A Faculty Development Program to Reduce Rater Error on Milestone-Based Assessments

Abstract: IntroductionCompetency-based assessment of resident performance requires faculty who are prepared to provide these assessments. Studies have shown that end-of-rotation evaluations completed by faculty lack reliability and fail to identify important deficiencies in residents' performance. 1,2A number of factors account for the less-than-acceptable reliability, including variations in clinical context or patient complexity, 3 lack of longitudinal experiences with residents and patients, 4 and rater error. Types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Faculty development has been proposed as a way of improving rater bias, 39,40 although such interventions could still result in faculty scores that are more lenient 41 or more stringent. 42 It has been suggested that residency programs can identify a subset of faculty dedicated to learning and performance assessments, and make them responsible for the majority of resident assessments. 41,42 Yet, others point out that this strategy might be less effective since medical raters may be unresponsive to professional development (e.g., Cook et al).…”
Section: Robustness and Dynamics Of Key Findingsmentioning
confidence: 99%
“…Faculty development has been proposed as a way of improving rater bias, 39,40 although such interventions could still result in faculty scores that are more lenient 41 or more stringent. 42 It has been suggested that residency programs can identify a subset of faculty dedicated to learning and performance assessments, and make them responsible for the majority of resident assessments. 41,42 Yet, others point out that this strategy might be less effective since medical raters may be unresponsive to professional development (e.g., Cook et al).…”
Section: Robustness and Dynamics Of Key Findingsmentioning
confidence: 99%
“…We assessed convergent validity using the residents’ ACGME Milestones scores; however, ACGME Milestones scores have been suggested to lack inter-rater reliability, and consistency between GME programs. 38 – 39 Moreover, the ACGME Milestones are not a complete determination of residents’ abilities nor do they assess all areas essential to unsupervised practice. 40 Finally, the ACGME Milestones were not designed to be an assessment tool in this context.…”
Section: Limitationsmentioning
confidence: 99%
“…14 Two studies determined that use of milestones was more effective than use of previous evaluation forms, and found better discrimination in ratings and a reduction in common rater errors. 15,16 On the other hand, a study of a milestone ''passport'' intervention in an emergency medicine program found only modest increases in resident satisfaction with feedback. 17 Another study reported that milestone-based assessments for end-of-shift evaluations led to grade inflation in an emergency medicine program.…”
Section: Figurementioning
confidence: 99%